Experimental testing of oil palm fibre composite manufactured via vacuum bagging method - Mohd Hafidz, N.S.; Mohamed Rehan, Muhammad Saifuddin (IOP Publishing Ltd, 2019)
The objective of this research is to compare tensile strength of oil palm fibre composite produced from oil palm fibre of different configurations. Compressed random oil palm fibre and uncompressed random oil palm fibre reinforced polyester composite were manufactured using vacuum bagging technique. The volume fractions of the fibre to the resin were 6.6:93.4 and 17:83 for compressed fibre and uncompressed fibre composites, respectively. The ratio of the polyester to hardener is 100:2. Tensile properties obtained via tensile tests as per ASTM D 638 specifications using Universal Testing machine INSTRON 5582. Load-displacement plots show that the fracture load and the slope for specimens from the same plate vary with a significant range. Stress-strain plots also have the same issue. With such data direct comparison of average value may not be giving a conclusive comparison, with a big standard deviation for both sets of specimens. Furthermore, there are two simultaneous factors in this study, namely the configuration of the oil palm fibres used and the volume ratio of the composite. Further testing and analysis is deemed to be necessary to further fine tune the fabrication process, for a conclusive comparison.